Engulfing a radio pulsar: the case of PSR J1023+0038 - Coti Zelati, F.; Baglio, M. C.; Campana, S.; D'Avanzo, P.; Goldoni, P.; Masetti, N.; Muñoz-Darias, T.; Covino, S.; Fender, R. P.; Jiménez Bailón, E.; Otí-Floranes, H.; Palazzi, E.; et al. (Monthly notices of the Royal Astronomical Society, 2014)
The binary millisecond radio pulsar PSR J1023+0038 has been recently the subject of multiwavelength monitoring campaigns which revealed that an accretion disc has formed around the neutron star (since 2013 June). We present here the results of X-ray and UV observations carried out by the Swift satellite between 2013 October and 2014 May, and of optical and NIR observations performed with the REM telescope, the Liverpool Telescope, the 2.1-m telescope at the San Pedro Mártir Observatory and the 1.52-m telescope at the Loiano observing station. The X-ray spectrum is well described by an absorbed power law, which is softer than the previous quiescent epoch (up to 2013 June). The strong correlation between the X-ray and the UV emissions indicates that the same mechanism should be responsible for part of the emission in these bands. Optical and infrared photometric observations show that the companion star is strongly irradiated. Double-peaked emission lines in the optical spectra provide compelling evidence for the presence of an outer accretion disc too. The spectral energy distribution from IR to X-rays is well modelled if the contributions from the companion, the disc and the intrabinary shock emission are all considered. Our extensive data set can be interpreted in terms of an engulfed radio pulsar: the radio pulsar is still active, but undetectable in the radio band due to a large amount of ionized material surrounding the compact object. X-rays and gamma-rays are produced in an intrabinary shock front between the relativistic pulsar wind and matter from the companion and an outer accretion disc. The intense spin-down power irradiates the disc and the companion star, accounting for the UV and optical emissions.